-3=b/3

Simple and best practice solution for -3=b/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=b/3 equation:



-3=b/3
We move all terms to the left:
-3-(b/3)=0
We add all the numbers together, and all the variables
-(+b/3)-3=0
We get rid of parentheses
-b/3-3=0
We multiply all the terms by the denominator
-b-3*3=0
We add all the numbers together, and all the variables
-1b-9=0
We move all terms containing b to the left, all other terms to the right
-b=9
b=9/-1
b=-9

See similar equations:

| 2(x-2)=-7x+41 | | 112+9x+5=180 | | 90÷d=-9 | | 298=x-36=24 | | 19=p-12;283031 | | 196+23x-2x=x-13 | | -8(t+35)+-48=48 | | 6x+3+33=180 | | 1/2(2x+16)=21 | | 7-2x÷6=x-5÷1 | | 15=(x-15) | | 90-41=x | | 4(w+347)+-71=29 | | 3/2x-3-5=19 | | 17^2x=17^5x-9 | | 715-z=602 | | -9(f+896)+-514=-190 | | (3+5x)+(6x+1)=180 | | 0=9p | | 42/x=20 | | 5.30x+2.50x+3=55.20 | | 3(h-92)=21 | | 7v+22=9(v+4) | | 9(b+20)+-39=-39 | | 28—4(x—5)=-4 | | 12n-1=8n+7 | | 4(h-71)=52 | | x-25=48 | | 5x+9-3x-4=-11 | | 97=9(p-88)+25 | | 42=6x-2 | | m^2=343 |

Equations solver categories